Assessment of Aflatoxin in Dairy Feeds, Milk, Blood and Evaluation of Mitigation Measures in North of Rift Valley Counties, Kenya - Ngaira , Victor M.; Oduho , George W.; Masinde , Japhether W.; Lusweti , Francesca N.; Kitilit , J. K.; Onyango , Ruth M. A. (African Journal of Education,Science and Technology (AJEST), 2013)
Aflatoxin is a group of mycotoxins produced by fungi that grow on food and feed materials. They are poisonous to animals and humans if consumption exceeds permissible levels. Their detrimental effects include drop in general animal productivity, increased disease incidences, chronic damage to vital organs and decreased reproductive performance. A survey was done in the North Rift region to investigate the prevalence of aflatoxin in dairy feeds. Feed samples from 16 farmers in three counties were collected by purposive sampling. The samples from the three counties were analyzed for aflatoxin B1. A four by four Latin Square experiment to assess the efficacy of calcium hydroxide, ammonium carbonate and brewer’s yeast to reduce aflatoxicosis in dairy cows was done. Samples of milk, blood and faecal material were collected at the end of each 7-day period. Feed and faecal samples were analyzed for aflatoxin B1 while milk and blood samples were analyzed for aflatoxin M1 using ELISA procedure. Statistical analysis of data on survey samples was done using SPSS for descriptive statistics while analysis of variance of experimental data was by SAS. The study revealed that all second grade maize samples obtained from the region was contaminated with aflatoxin B1, the highest concentration of 15.5 ppb being recorded in Cherangani while lowest concentration of 0.01 ppb was in Nandi County. The overall means for aflatoxin concentration was 1.210 ppb.The effects of calcium hydroxide, ammonium carbonate or brewer’s yeast milk production, Aflatoxin M1 in milk and in blood were not significant (P>0.05), but significantly altered the amount of aflatoxin B1 in faeces (p< 0.05). The aflatoxin M1 content in milk and blood was 0.196 and 0.018 ppb respectively. The percentage of feed aflatoxin in milk and blood was 0.997 % and 0.078 % respectively. Treatment of alkaline compounds and Brewer’s yeast as used in this study did not reduce aflatoxin M1 in milk and blood but, had a significant effect on aflatoxin B1 in faeces.